Investigating the short- and long-term effects of antibacterial agents using a real-time assay based on bioluminescent E. coli-lux - Suominen Eetu; Putus Tuula; Atosuo Janne (Elsevier, 2022)
We have previously established that the E. coli-lux assessment is a convenient tool for rapid measurements of the kinetical features of short-term toxicity caused by various factors. In this study, kinetic measurements of seven specifically acting model antibacterials (i.e., polymyxin B, chloramphenicol, nalidixic acid, kanamycin, deoxynivalenol, erythromycin and tetracycline) and two metals (AgNO3 and CdCl2) against E. coli-lux through a bioluminescence- and optical density-based real-time assay that combined short- and long-term toxicity assessments were performed. Bacteria were exposed to antibacterials and the effects were reported as the half-maximum effective concentration (EC50) after 30 min and 10 h. Regarding the 10-hour endpoints, all reference compounds, except deoxynivalenol, showed dose-response inhibition in the studied concentration range. The analysis of chloramphenicol, kanamycin, erythromycin, tetracycline and nalidixic acid clearly revealed the limitations of short-term inhibition tests. No significant differences were observed between the results obtained from luminescence inhibition and growth inhibition assays. The kinetical data from measurements provide differentiation between bacteriostatic and bactericidal mechanisms of various types of antibacterial agents. The combined assessment of short- and long-term effects reduces the risk of the underestimation of toxicity due to an inaccurate endpoint selection. The cost-efficient and fully automated E. coli-lux assessment technique may offer possibilities for high-throughput screening procedures.